The Effectiveness of Phosphate Solubilizing Rhizobacteria on The Growth and Yield of Several Soybean Varieties on Ultisol Soils - Diyanti, Afri R.; Utama, M Z.H.; Ernita, Milda (Akta Agrosia, 2020)
ABSTRACH  This study aims to obtain  the interaction of rhizobacteria and soybean varieties, types of rizobacteria that  effectively  dissolve phosphate, varieties that  are able to grow well on ultisol soils. The research is rizobacterial isolation and rizobacteria selection. Observations made were bacterial isolation, identification of morphological and physiological rhizobacteria (gram  reactions, hypersensitive reactions, as phosphate solvents and germination test and rhizobacteria test of phosphate solvents by inplanta. The results showed that  rizobacteria isolates from ultisol soil of chilli plants, eggplant plants and rice roots obtained 32 isolates. The highest number of isolates were obtained from the ultisol soil of chilli plants namely  18 isolates. The color of the rizobacteria isolate colony was obtained by 27 cream isolates and 5 yellow isolates. The surface of the colony in the chilli ultisol soil consisted of 3 groups namely  arising, flat and convex, the surface of the colony arising obtained 8 isolates, the flat surface obtained 9 isolates and the convex  surface obtained 1 isolate. All isolates were gram negative. From 32 rizobacteria isolates, there  were 2 isolates which were able to dissolve phosphate, namely  RT1 and RC3. In green  bean  plants with RT1 administration, the seeds weight was 2.76 grams high compared to control  and RC3. Key words: Rhizobacteria solvent phosphate RT1, RC3, ultisol, mung  bean